Exhaled gas detection by a novel Rh-doped CNT biosensor for prediagnosis of lung cancer: a DFT study. (2nd September 2018) - Wan, Qianqian; Xu, Yancheng; Chen, Xiaoqi; Xiao, Hanyan
ABSTRACT: Lung cancer has received considerable attention in recent years due to its high mortality. The difficulty in awareness of such disease can be attributed to its strong insidiousness during the early stage. Therefore, the prognosis of lung cancer becomes significant so as to nip this disease in the bud. In this paper, the Rh-doped CNT-based biosensors were introduced to realise the diagnosis of lung cancer through detecting the exhaled gas of possible patients. The adsorption property and sensing mechanism of Rh-CNT towards two kinds of mainly typical gases of lung cancer, namely, C6 H6 and C6 H7 N, were analysed based on density functional theory, aiming at evaluating the potential application of such material to be gas sensors. The results indicated that the Rh-CNT not only has good adsorption towards such two gases but also obvious conductivity increase when interacted with any of them, while presents insensitivity upon the common exhaled gas, CO2 . We suggest the Rh-CNT be prepared as biosensors applied in the field of lung cancer pre-diagnosis that can be used in our daily life without pain and complex clinical examination. GRAPHICAL ABSTRACT: